Bioengineered carboxymethyl cellulose-doxorubicin prodrug hydrogels for topical chemotherapy of melanoma skin cancer. (1st September 2018) - Capanema, Nádia S.V.; Mansur, Alexandra A.P.; Carvalho, Sandhra M.; Carvalho, Isadora C.; Chagas, Poliane; de Oliveira, Luiz Carlos A.; Mansur, Herman S.
Graphical abstract: Highlights: Carboxymethyl cellulose-doxorubicin bioconjugates (CMC-DOX) were synthesized. CMC-DOX polymer-drug hydrogels were synthesized by crosslinking with citric acid. Degree of substitution (DS) of CMC tuned the properties of the bioconjugate hydrogels. CMC-DOX polymer-drug hydrogels modulated the kinetics of in vitro DOX release profile. New CMC-DOX polymer-drug hydrogels were effective against skin melanoma cancer cells. Abstract: Melanoma is the most aggressive type of skin cancer with high rates of mortality. Despite encouraging advances demonstrated by anticancer drug carriers in recent years, developing ideal drug delivery systems to target tumor microenvironment by overcoming physiological barriers and chemotherapy side effects still remain intimidating challenges. Herein, we designed and developed a novel carbohydrate-based prodrug composed of carboxymethylcellulose (CMC) polymer bioconjugated with anticancer drug doxorubicin hydrochloride (DOX) by covalent amide bonds and crosslinked with citric acid for producing advanced hydrogels. The results demonstrated the effect of CMC hydrogel network structure with distinct degree of substitution of carboxymethyl groups of the cellulose backbone regarding to the process of bioconjugation and on tailoring the DOX release kinetics in vitro and the cytotoxicity towards melanoma cancer cells in vitro . To this end, an innovative platform was developed based on polysaccharide-drug hydrogels offering promising perspectives for skin disease applications associated with topical chemotherapy of melanoma.